FLIP AND SWITCH - MINORITY AND CULT FILM IN INDONESIAN CINEMA - Ahmad Riza Faizal (Ikatan Sarjana Komunikasi Indonesia, 2017)
This research has put forward the Flip and Switch concepts as milestones for signifying when a film narrative change their syntagmatic course through characters back and forth in weight and position thus change the messages that might be conveyed by the spectators about the film. The concepts were pointed by using the semiotic rectangle, or also known as The Greimasâ€™ rectangle, about minority issues in one of the best Indonesian film ever made, Cahaya dari Timur: Beta Maluku. This research found two flips and two switches which signify changes in course and narrative patterns through out the film. By using criterion of what makes a film become a cult film, the research sorted and opted several peculiar scenes. Those scenes can leads the film become a cult film if the phenomena criteria are lifted and established over time. Nevertheless, at present, the film Cahaya dari Timur: Beta Maluku is not yet a cult film. Related to minority issues, the film comes from a non Anti-minority issues which complements with anti-minority issues, these findings signified that Cahaya dari Timur: Beta Maluku is not a film about minority issues but what has became after all those minority conflicts are solved.Â